ANALISIS KEMUDAHAN DAN PENERIMAAN PENGGUNAAN REKAM MEDIS ELEKTRONIK (RME) DI INSTALASI RAWAT JALAN RSUD DR. SOEDONO MADIUN : TECHNOLOGY ACCEPTANCE MODEL - Fadhilah, Kiki Maharani; Hidayat, Darsun; Rohendi, Acep (JURNAL PENELITIAN TERAPAN KESEHATAN, 2025)
The development of health information technology brings changes in the social interaction model that affects the way of communication and interaction both internally and externally in hospitals. The use of Electronic Medical Records (EMR) is one form of SIMRS implementation that is expected to integrate hospital health services with patient treatment history. The existence of obstacles in the form of generation gaps and technological stuttering in the use of EMR, it is necessary to consider whether the relevant parties can adapt to the way EMR works so that it requires a period of time and technological adjustments. The Technology Acceptance Model (TAM) is one method of evaluating the success of technology implementation. The purpose of this study was to determine the effect of employee characteristics on the acceptance and use of electronic medical records (EMR) in the Outpatient Installation of dr. Soedono Madiun Hospital. The number of respondents in this study was 70 people. This type of research is descriptive analytical where the emphasis is on quantitative research to analyze the correlation between variables related to the use of EMR. The research instrument used a questionnaire and documentation. Based on the research results, it shows that employee characteristics do not affect the perception of ease and usefulness of using RME, perception of ease of use affects perception of usefulness, perception of ease of use and perception of usefulness affect employee attitudes and acceptance, employee attitudes affect behavioral intentions of use, and behavioral intentions of use do not always continue to actual use.